High serum prevalence of autoreactive IgG antibodies against peripheral nerve structures in patients with neurological post-COVID-19 vaccination syndrome - Arlt, Friederike A.; Breuer, Ameli; Trampenau, Elli; Boesl, Fabian; Kirchner, Marieluise; Mertins, Philipp; Sánchez-Sendín, Elisa; Nasouti, Mahoor; Mayrhofer, Marie; Blüthner, Martin; Endres, Matthias; Prüss, Harald; et al. (Frontiers in Immunology, 2024)
Background: Patients suffering from neurological symptoms after COVID-19 vaccination (post-COVID-19 vaccination syndrome (PCVS)) have imposed an increasing challenge on medical practice, as diagnostic precision and therapeutic options are lacking. Underlying autoimmune dysfunctions, including autoantibodies, have been discussed in neurological disorders after SARS-CoV-2 infection and vaccination. Here, we describe the frequency and targets of autoantibodies against peripheral nervous system tissues in PCVS.Methods: Sera from 50 PCVS patients with peripheral neurological symptoms after COVID-19 vaccination and 35 vaccinated healthy controls were used in this study. IgG autoreactivity was measured via indirect immunofluorescence assays on mouse sciatic nerve teased fibers. The frequencies of autoantibodies were compared between groups using Fisher's exact test. Serum antiganglioside antibodies were measured in ganglioside blots. Autoantibody target identification was performed using immunoprecipitation coupled to mass spectrometry. Subsequent target confirmation was conducted via cell-based assays and ELISA.Results: Compared with controls, PCVS patients had a significantly greater frequency of autoantibodies against peripheral nervous system structures (9/50(18%) vs 1/35(3%); p=0.04). Autoantibodies bound to paranodes (n=5), axons (n=4), Schmidt-Lanterman incisures (n=2) and Schwann cell nuclei (n=1). Conversely, antibodies against gangliosides were absent in PCVS patients. Target identification and subsequent confirmation revealed various subunits of neurofilaments as well as DFS-70 as autoantibody epitopes.Conclusion: Our data suggest that autoantibodies against nervous system tissue could be relevant in PCVS patients. Autoantibodies against neurofilaments and cell nuclei with so far non-established links to this disease spectrum should be further elucidated to determine their biomarker potential.